Barriers to the implementation of programs for the prevention of mother-to-child transmission of HIV: A cross-sectional survey in rural and urban Uganda - Bajunirwe, Francis; Muzoora, Michael (AIDS Research and Therapy, 2005)
Background: Implementation of programs for the prevention of mother-to-child transmission (PMTCT) of HIV faces a variety of barriers and challenges. The assessment of these challenges has generally been conducted in large urban health facilities. As programs expand into rural areas, the potential barriers that may be encountered there also need to be assessed. This study examines potential barriers that might affect the acceptability of interventions for PMTCT in rural and urban settings. Results: Four hundred and four women at a large urban hospital and three rural clinics that had recently started implementing PMTCT were interviewed. Level of knowledge of MTCT and preference for rapid HIV testing were equally high in both areas, but rural women had a higher tendency to think that they should consult their husbands before testing, with borderline statistical significance (72% vs. 64% p = 0.09). Health facility-based deliveries were significantly lower among mothers in rural areas compared to those in the urban setting. Overall, significant predictors of willingness to test for HIV were post-primary education (OR = 3.1 95% CI 1.2, 7.7) and knowledge about rapid HIV tests (OR = 1.8, 95% CI 1.01, 3.4). The strongest predictor of willingness to accept an HIV test was the woman's perception that her husband would approve of her testing for HIV. Women who thought their husbands would approve were almost six times more likely to report a willingness to be tested compared to those who thought their husbands would not approve (OR = 5.6, 95% CI 2.8, 11.2). Conclusion: Lessons learned in large urban hospitals can be generalized to rural facilities, but the lower proportion of facility-based deliveries in rural areas needs to be addressed. Same-day results are likely to ensure high uptake of HIV testing services but male spousal involvement should be considered, particularly for rural areas. Universal Primary Education will support the success of PMTCT programs.
Keywords: Mother-to-child transmission; HIV; cross-sectional survey; Rural and urban; Uganda